Female Learners Expectations and Experiences in Open and Distance Learning: Case of the University of Lagos - Ebabhi, Abosede Margaret; Adewoyin, A. D. (NIU Journal of Humanities, 2020)
The education of the female child has remained constant in the frontline of global discuss. Open and Distance Learning (ODL) contributions towards attaining the sustainable development goal five which is to achieve gender equality and empower all women and girls cannot be overstated. ODL is an avenue to bridge the disparity of gender education through the open and flexible learning policy. Female enrolment into ODL programmes is globally on the increase. This study therefore aimed at investigating the expectations and experiences of female learners in ODL using Distance Learning Institute, University of Lagos as the locale of the study. The objectives of the study were to examine issues affecting female learners in ODL, investigate the expectations of female learners when enrolling in ODL, to investigate their experiences and the process of meeting female learnersâ€™ expectations. A descriptive survey was used to obtain the information. A validated structured questionnaire was used to obtain information from 380 sampled female learners of the 7,600 target population of female learners. The data was analyzed using descriptive statistical method. The findings revealed that majority of the respondents were married and have one form of employment or the other though faced with a number of challenges that hinder their studies such as psychological and emotional stress for expectant mothers and lack of financial support. They also have great expectations such as acceptance and respect among peers, obtaining higher qualification to bridge the gap of gender disparity in work places as well as raising the standard of living for their families. The study therefore recommends that government and all necessary stakeholders should provide incentives that would make the programme less stressful for the learners and grant bursary to female learners to alleviate their financial status. Keywords:   Education, Expectation, Female, Learners, Open Distance